PS4:82 Lupus pregnancy: achievements and open issues in the multidisciplinary management. (21st March 2018) - Crisafulli, F; Andreoli, L; Antolini, L; Parma, G; Benigno, C; Lojacono, A; Zatti, S; Cappa, V; Calza, S; Tincani, A
Abstract : Purpose: To analyse the pregnancy outcome of patients with Systemic Lupus Erythematosus (SLE): by comparing the outcome of prospectively–followed pregnancies (PFP) and anamnestic pregnancies (AP); by comparing the outcome of PFP with the general obstetric population (GOP); by evaluating the disease features, maternal risk factors and treatment of pregnancies with adverse pregnancy outcome (APO) in PFP. Methods: A monocentric, retrospective and observational study of 94 SLE patients with a total of 135 pregnancies followed prospectively by multidisciplinary team. In addition, 33 AP in the same SLE patients and 3939 pregnancies among GOP were evaluated. Clinical and serological data were obtained from medical records. Results: The comparison between PFP and AP showed lower frequency of premature miscarriage (6, 7% vs 27, 3%, p value 0, 0021) and fetal death (3, 7% vs 36, 4%, p value<0, 0001) and higher frequency of live birth (88, 9% vs 36, 4%, p value<0, 0001) in the first group. As compared with GOP, SLE-PFP displayed similar rate of early miscarriage (9, 0% vs 6, 7%) and fetal loss (5, 0% vs 3, 7%) but higher frequency of preeclampsia (1, 0% vs 5, 0%, p value 0, 0029), preterm birth (7, 0% vs 18, 4%, p value<0, 0001) and Caesarian section (31, 0% vs 41, 7%, p value 0, 0288). APO occurred in 17 (12.6%) of the 135 PFP. Despite the lack of statistical significance, there was a tendency toward higher frequency of anti-dsDNA positivity (84, 6% vs 62, 6%), history of lupus nephritis (52, 9% vs 33, 0%) and triple anti-phospholipid antibody (aPL) positivity (23, 5% vs 11, 8%) in pregnancies with APO (table 1). Analysing treatment during pregnancy, the group with APO received higher doses of prednisone (without significant p value) and required higher use of immunosuppressants (64, 7% vs 31, 3%, p value 0, 032). Conclusions: The outcome of PFP in SLE has dramatically improved as compared to AP, thanks to pregnancy planning, multidisciplinary management and close monitoring during pregnancy. The occurrence of APO was restricted to a minority of PFP (12, 6%). SLE-PFP had similar rates of pregnancy losses as compared to GOP, but there are still open issues on some pregnancy complications that affect SLE patients more frequently.